Psikoedukasi Literasi Kesehatan Mental Remaja di Desa Pasir Tanjung, Kec. Tanjungsari, Kabupaten Bogor, Jawa Barat - Zakiah, Ernita; Akbar, Zarina; Mauna; Khoiruningrum, Lulu; Ardyagarini Nugroho, Pramudya; Nur Khofifah, Khadijah (Universitas Negeri Jakarta, 2023)
Teenagers lack of understanding about mental health literacy is a very important thing to pay attention to. Not a few teenagers experience mental health problems such as stress, depression, anxiety disorders, mood disorders, and others, but they do not receive optimal treatment because they do not have good mental health literacy. Therefore, psychoeducation is needed to help teenagers become more familiar with mental health literacy. This psychoeducation aims to increase mental health literacy among teenagers in Pasir Tanjung. Psychoeducation is delivered using the lecture method. The participants were 27 teenagers in Pasir Tanjung. This psychoeducation program went according to plan and without significant obstacles. Participants also seemed enthusiastic and eager to take part in the activities carried out.